Strategic Analysis in Research Reactor Management - Solís Pillaca, Rocío Del Pilar (2023)
Research reactors play a fundamental role in the development of peaceful applications of nuclear energy. This encompasses their contributions to medicine, industry, science, research and education. Strategic planning is therefore required to take full advantage of their use. To this end, the SWOT tool was employed as the basis for the strategic analysis and planning required to manage the utilization of research reactors, the result of which makes it possible to identify the needs of all stakeholders as well as manage their impact in order to make timely decisions with the goal of ensuring the continuity of the existing research reactor’s safe and continuous operation in the context of a potential investment in the modification and expansion of its facilities.